2008
DOI: 10.1016/j.rasd.2007.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Positive behavioral and electrophysiological changes following neurofeedback training in children with autism

Abstract: Two electrophysiological studies tested the hypothesis that operant conditioning of mu rhythms via neurofeedback training can renormalize mu suppression, an index of mirror neuron activity, and improve behavior in children diagnosed with autism spectrum disorders (ASD). In Study 1, eight high-functioning ASD participants were assigned to placebo or experimental groups before 10 weeks of training of the mu frequency band (8-13 Hz). Following training, experimental participants showed decreased mu power and cohe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
107
3
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(121 citation statements)
references
References 66 publications
6
107
3
4
Order By: Relevance
“…The advantage of using these comprehensive parental assessments is that behavioral changes in the real-world rather than in laboratory settings can be determined, whereas the disadvantage is that they could be biased by parental expectations. Pineda et al (2008) have previously reported improvements in the ATEC due to mu-based NFT in comparison to a control group receiving placebo feedback. In the current study, significant improvements in autistic symptoms, social responsiveness and adaptive behavior were shown in the post-compared to pre-test equally for both groups.…”
Section: Changes In Behavior Assessed By the Parentsmentioning
confidence: 98%
See 2 more Smart Citations
“…The advantage of using these comprehensive parental assessments is that behavioral changes in the real-world rather than in laboratory settings can be determined, whereas the disadvantage is that they could be biased by parental expectations. Pineda et al (2008) have previously reported improvements in the ATEC due to mu-based NFT in comparison to a control group receiving placebo feedback. In the current study, significant improvements in autistic symptoms, social responsiveness and adaptive behavior were shown in the post-compared to pre-test equally for both groups.…”
Section: Changes In Behavior Assessed By the Parentsmentioning
confidence: 98%
“…2 (Oberman et al 2005;Pineda et al 2008). Participants were asked to watch six 1-min videos twice in random order.…”
Section: Pre-and Post-tests: Evaluation Of Training Successmentioning
confidence: 99%
See 1 more Smart Citation
“…We 615 propose that this differentiation might subserve different cognitive operations during action 616 observation vs action execution. Eventually, the reported functional dissociation between alpha 617 and beta bands may have an impact in clinical applications such as the neurological rehabilitation 618 based on the ”--rhythm neurofeedback (Pineda et al, 2008). In fact, a lack of ” suppression has 619 been hypothesized as an electrophysiological correlate of the putative Mirror Neuron Systemautism spectrum disorder (ASD) (Rizzolatti et al, 2009 …”
Section: ) 527mentioning
confidence: 99%
“…NFT research from our laboratory, reviewed in more detail by Pineda et al (2014a), has targeted mu waves by up-training 8-12 Hz rhythms over the central motor strip while inhibiting beta and theta waves (which are associated with general movement and eye blinks, respectively). Results suggest that learning to control mu-related oscillations though NFT can normalize mu suppression during action observation tasks and improve behavior in individuals with ASD and an IQ > 80 (Datko et al 2017;Pineda et al 2008;Pineda et al 2014a;Friedrich et al 2015). Relevant criticisms of these studies have highlighted potential confounds, such as the control of attentional factors, highly localized evidence of the effect NFT on neurophysiology, and the overlap of occipital alpha with the mu frequency band.…”
mentioning
confidence: 99%